The Effect of Occlusion on Temporomandibular Joint Dysfunction - Çağrı Ulusoy; Nilüfer Darendeliler (Galenos Yayinevi, 2008)
Temporomandibular disorders (TMD) are a combination ofpathologic and functional situations affecting the temporomandibular joint (TMJ) and the masticatory muscles. The dental community has become increasingly interested in TMD-occlusion relationship, however there are so many different and conflicting opinions about this issue. The aim of this study was to compare the prevalance of molar relationship, occlusal guidance (canine and group function) and non-working side contacts in symptomatic and asymptomatic patients with temporomandibular disorders (TMD). This study was based on the records of 108 dental students with a mean age of 23,19±2,06 years. Occlusal factors and the TMD symptoms were recorded and the relations between these criteria were evaluated. The relation between the type of laterotrusive movement and the the teeth contacts on the balancing side was found to be statistically significant (P<0.001) and the correlation between the intermolar relation and the protrusion contacts reached a level of significance, (P<0.01). Depending on the findings of this study, occlusion is expected to have some effect in the laterotrusive and protrusive mandibular movement.